INTRODUCTION TO MICROALGAE CULTIVATION TO IMPROVE SCIENTIFIC CRITICAL THINKING SKILLS IN SMAN 4 PALANGKA RAYA - Faridah Tsuraya; Widya Krestina; Desimaria Pandjaitan; Vinsen Willi Wardhana (Universitas Airlangga, 2026)
Scientific critical thinking skills are key to helping students gain a deep understanding of concepts, create innovative solutions, and apply scientific principles in real life. The objective of this community service is to introduce microalgae cultivation to enhance the scientific critical thinking skills of students at SMAN 4 Palangka Raya. The methods used to carry out this community service activity included identification and preparation, a pre-test, implementation of the activity (presentation of material and laboratory practice with inquiry methods), a post-test, and evaluation. This activity was attended by approximately 40 students in one class, all of whom were science majors. The results of this activity showed a pre-test score of 59.13, a post-test score of 74.34, and an increase in scores from the pre-test to the post-test of 15.21, representing a 26% increase. Students also demonstrated a better understanding of critical questions regarding microalgae cultivation methods (reaching 13%) compared to questions regarding the definition of microalgae (6%). Testimonials from student representatives indicated that the students enjoyed learning about this topic. This activity also left a positive impression on the students because they enjoyed participating in a science learning activity that is not typically taught in school. This community service activity was found to improve the scientific critical thinking skills of students at SMAN 4 Palangka Raya, as evidenced by an increase in scores from the pre-test to the post-test and based on direct observations of students’ questions and answers. Based on these results, it was found that inquiry-based learning in this community service can indirectly improve students’ critical thinking skills, even though it was conducted on only one simple topic.